Agregação de valor pelo agroturismo: um estudo na cadeia produtiva do café em Araponga – MG - Andrade, Helga Cristina Carvalho de (2015)
At the end of the 20th century, new consumption needs promote specialty coffees that ensures a privileged place for coffee in the gastronomy and awakens interest in the production origin. It is therefore noticed a growing interest in penetrating the tourism sector from rural producers attracted by the expectation of the added value of the coffee. This phenomenon means the creation of new governing structures in the coffee production line and inaugurates a new dynamic in the production environment. This research aims at verifying how the structure and dynamic of the coffee production line can help increase the touristic appeal in Araponga –MG, contributing to the added value in products and services linked to the coffee-growing. For this purpose, the research uses the constructs of the Transition Cost Economics to analyse the interfaces between the coffee producing chain and the agrotourism from the perspective of three coffee producers from Araponga, in Minas Gerais, participants of the Coffee and Cachaça Route. The research has been descriptive and quantitative based on primary (interviews) and secondary data. To analyse the primary data, the transcription of interviews and the analysis of its content have been used. The results have shown that the interviewed producers perceive the organizational environment in different ways. It has been identified “assets specificities” of all types indicated in the literature besides the high strategic value of such assets. In relation to “uncertainties”, evidences of primary, secondary and behaviourist uncertainty have been found. The attribute “frequency” is seen as medium or high by the three producers even though the transactions mean low volume of coffee or visitants. In regards to the behaviour of the agents, opportunist actions have been noted in the relation between owners and workers and among the owners. The governance structure of each property is different; however, the three producers strengthened their relations with the final consumers. It is also outstanding that the assets of the coffee production show a high touristic appeal from the technical, ludic and commercial point of view. This appeal is higher during the coffee‟s harvesttime. The added value is perceptible by the prices increase and the production verticalisation. Nevertheless, it has been noted that the added value of the product has been the trigger for touristic visits and not the contrary. The touristic entrepreneurial coffee producers see diversification as a way to expand the market. The great benefit from the introduction of tourism in the properties is the opportunity for rural families to achieve better living and working standards.